1998
DOI: 10.1136/ard.57.9.527
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of cartilage oligomeric matrix protein and bone sialoprotein in hip osteoarthritis: A one year prospective study

Abstract: Objective-To evaluate serum concentations of cartilage oligomeric matrix protein (COMP) and bone sialoprotein (BSP) as predictors of disease progression in hip osteoarthrtitis (OA). Methods-Forty eight consecutive patients, referred to hospital for symptomatic hip OA, (ACR criteria) were monitored in a one year prospective trial with radiographs and serum samples. The radiographs were graded for joint space narrowing, osteophytes, and sclerosis and the joint space width was measured by a digitised image analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
5
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 30 publications
5
65
5
3
Order By: Relevance
“…Predictive values of serum levels of C-reactive protein (43), COMP (44,45), and hyaluronic acid (46) have been found in some studies, but not in all (47). However, molecular markers investigated in these studies were not specific to joint tissue (6), and none of the studies evaluated the metabolism of type II collagen, the most abundant protein of cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive values of serum levels of C-reactive protein (43), COMP (44,45), and hyaluronic acid (46) have been found in some studies, but not in all (47). However, molecular markers investigated in these studies were not specific to joint tissue (6), and none of the studies evaluated the metabolism of type II collagen, the most abundant protein of cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CRP levels were greater with more severe hip OA (1.3-2.9 times greater, effect size d = 1.2-1.8) than those with less severe OA. Increased levels of cartilage oligomeric protein (COMP) were associated with increasing hip OA severity in one study (effect size d = 4.9) [15] but not in three other studies [6,14,20]. However, a recent study [6] demonstrated increased levels of deamidated COMP (DCOMP) to be associated with increasing hip OA severity as measured by the Kellgren-Lawrence grade, whereas COMP demonstrated no association.…”
Section: Disease Stagingmentioning
confidence: 93%
“…Control [1,5,12,18,19,49]; atrophic versus hypertrophic in two studies [13,14]; and radiographic OA classification in five studies [6,23,42,47,48]. Two studies [15,20] analyzed minimum joint space width as a continuous variable relative to biomarker levels. Eleven ''progression'' studies [7-9, 15, 17, 24, 29, 30, 35, 37, 39] investigated the association of 13 different biomarker levels with the progression of hip OA.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations